Pengaruh Pijat Bayi untuk Meningkatkan Status Kesehatan Anak Bayi 1-12 Bulan - Syuhrotut Taufiqoh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to identify the effect of infant massage in improving the health status of infants 1-12 monthsMethods: This study is a pre-experimental study with one group-test pre-post test design This study uses an observation sheet where baby weight weighing is carried out before the baby massage (Pretest) and after the baby massage (Posttest) in the group is carried out. Massage is done 2 times / week during 10- 15 minutes for 4 weeks assessed with a checklist sheet. The unit of analysis is children under one year old totaling 30 babies. Wilcoxon Test Sample analysis, which is to determine the difference in treatment in two samples / treatment groups on the condition that the data is normally distributed.Results: complaints of babies aged 1-12 months before stimulation of baby massage, most of the respondents had complaints experienced by babies were runny nose (40%), cough (30%), fever (27%) and no complaints (7%) and after a baby massage, complaints of colds were 5 respondents (16%), cough 2 respondents (7%), and heat respondents of 1 person (4%) and no complaints (73%). Researchers conducted a statistical test wilcoxon obtained a significant figure (0.000) much lower than a significant standard of 0.05, which means that there is an effect of Massage on the health status of babies aged 1-12 months at PMB Siti Alfiyah SurabayaConclusion: In this study, it was concluded that there was a significant influence of giving baby massage on the health status of babies at the age of 1-12 months. Researchers found complaints such as cough, runny nose, higher heat occurred in babies before baby massages